Clinical-diagnostic and therapeutic landmarks of conversion disorder. Literature synthesis - Prihor, Mădălina Dumitrița; Bolos, Alexandra; UNTU, Ilinca; Chirita, Roxana (Buletin de psihiatrie integrativa, 2021)
Conversion disorder, a pathology always present in the current practice of psychiatrists, being the subject of multiple empirical research in the early twentieth century, is now a little explored nosological category, the literature having many gaps in its therapeutic landmarks. The present synthesis of the specialized literature aims to draw attention to the importance of studying this topic and the favorable consequences that can establish a comprehensive clinical-therapeutic guide in terms of addressing the conversion disorder, by limiting patient addressability in general medical centers and in emergency rooms, by streamlining the exclusion of organic diseases and by increasing the quality of life of people suffering from this disorder.